Does High Public Trust Amplify Compliance with Stringent COVID-19 Government Health Guidelines? A Multi-country Analysis Using Data from 102,627 Individuals - Pak A; McBryde E; Adegboye OA (Dove Medical Press, 2021)
Anton Pak,1 Emma McBryde,1 Oyelola A Adegboye1,2 1Australian Institute of Tropical Health and Medicine, James Cook University, Townsville, QLD, Australia; 2Public Health & Tropical Medicine, College of Public Health, Medical and Veterinary Sciences, James Cook University, Townsville, QLD, AustraliaCorrespondence: Oyelola A AdegboyePublic Health & Tropical Medicine, College of Public Health, Medical and Veterinary Sciences, James Cook University, 1 James Cook Drive, Townsville, Queensland 4814, AustraliaEmail oyelola.adegboye@jcu.edu.auPurpose: To examine how public trust mediates the people’s adherence to levels of stringent government health policies and to establish if these effects vary across the political regimes.Methods: This study utilizes data from two large-scale surveys: the global behaviors and perceptions at the onset of COVID-19 pandemic and the Oxford COVID-19 Government Response Tracker (OxCGRT). Linear regression models were used to estimate the effects of public trust and strictness of restriction measures on people’s compliance level. The model accounted for individual and daily variations in country-level stringency of preventative measures. Differences in the dynamics between public trust, the stringent level of government health guidelines and policy compliance were also examined among countries based on political regimes.Results: We find strong evidence of the increase in compliance due to the imposition of stricter government restrictions. The examination of heterogeneous effects suggests that high public trust in government and the perception of its truthfulness double the impact of policy restrictions on public compliance. Among political regimes, higher levels of public trust significantly increase the predicted compliance as stringency level rises in authoritarian and democratic countries.Conclusion: This study highlights the importance of public trust in government and its institutions during public health emergencies such as the COVID-19 pandemic. Our results are relevant and help understand why governments need to address the risks of non-compliance among low trusting individuals to achieve the success of the containment policies.Keywords: public trust, stringency, compliance, SARS-CoV-2, COVID-19, public health